Engineering of Shewanella marisflavi BBL25 for biomass-based polyhydroxybutyrate production and evaluation of its performance in electricity production - Lee, Sun Mi; Lee, Hong Ju; Kim, Sang Hyun; Suh, Min Ju; Cho, Jang Yeon; Ham, Sion; Song, Hun Suk; Bhatia, Shashi Kant; Gurav, Ranjit; Jeon, Jong Min; Yoon, Jeong Jun; Choi, Kwon Young; et al. (International Journal of Biological Macromolecules, 2021)
Polyhydroxybutyrate (PHB) is a biodegradable plastic with physical properties similar to petrochemically derived plastics. Here, Shewanella marisflavi BBL25 was engineered by inserting the pLW487 vector containing polyhydroxyalkanoates synthesis genes from Ralstonia eutropha H16. Under optimal conditions, the engineered S. marisflavi BBL25 produced 1.99 ± 0.05 g/L PHB from galactose. The strain showed high tolerance to various inhibitors and could utilize lignocellulosic biomass for PHB production. When barley straw hydrolysates were used as a carbon source, PHB production was 3.27 ± 0.19 g/L. In addition, PHB production under the microbial fuel cell system was performed to confirm electricity coproduction. The maximum electricity current output density was 1.71 mA/cm2, and dry cell weight (DCW) and PHB production were 11.4 g/L and 6.31 g/L, respectively. Our results demonstrated PHB production using various lignocellulosic biomass and the feasibility of PHB and electricity production, simultaneously, and it is the first example of PHB production in engineered Shewanella.
Keywords: Bacterial Proteins; Biomass; Cupriavidus necator; Galactose; Genetic Engineering; Hordeum; Hydrolysis; Hydroxybutyrates; Plasmids; Polyhydroxyalkanoates; Shewanella; Electricity; Polyhydroxybutyrate (PHB); Shewanella marisflavi BBL25